Existence oF Salmonella sp. in Beef Meat In Sangatta, Kutai Timur District - Rustam Rustam; Mey Angraeni Tamal; Joni Ariansyah (Hasanuddin Journal of Animal Science (HAJAS), 2019)
Based on microbiological aspects, product of an animal food safe to be consumption if not contain microbial pathogens, microbial that can cause health problems of humans to whom comsume it, one of the pathogenic bacteria that often found on beef is a salmonella sp. Research aimed to determine the existence of bacteria Salmonella sp from slaughterhouse, abattoir and traditional market in Sangatta East Kutai regency. Parameter research parameter of observation was to determine whether there are bacteria Salmonella sp (positive / negative) on beef samples and how much percentage (%) the existence of Salmonella sp on beef samples. obtained data for each test were analyzed by descriptive approach. Based on research results on 20 beef samples both from slaughterhouses, abattoir, and sold in Sangatta traditional market not indicate the existence of bacteria Salmonella sp (negative), possibility it is because growth of bacteria Salmonella sp still low and does not have the ability to compete with bacteria lactic acid (Streptococcus, Lactobacillus, Aeromonas, Acenetobacter, Pseudomonas) so that growth will be obstructed.